Bioremediation of degraded pit mud by indigenous microbes for Baijiu production. (December 2022) - Liu, Mao-Ke; Liu, Cheng-Yuan; Tian, Xin-Hui; Feng, Jun; Guo, Xiao-Jiao; Liu, Ying; Zhang, Xin-Yu; Tang, Yu-Ming
Abstract: Microbes in pit mud play key roles in fermentation cellars for Chinese strong-flavor Baijiu (SFB) production. Pit mud, however, is frequently degraded during production, compromising the quality of the end product. In this study, a bioremediation method was used to restore degraded pit mud (DPM) using indigenous microbes derived from SFB production. Metabolomics and metagenomics were used to determine the dynamics of prokaryotes during DPM restoration and their link to SFB production. The composition of flavor compounds in SFB changed ( P  = 0.0001) before and after restoration of DPM. Consistent with the improved sensory quality, the ethyl caproate/ethyl lactate ratio, an SFB quality measure, increased after restoration ( P  < 0.001). The concentrations of humus, NH4 +, available phosphorus, and available potassium in DPM increased during the restoration process ( P  < 0.05), which is consistent with high-quality pit mud. The relative abundance of microbes that are beneficial to SFB fermentation, such as Caproiciproducens, a bacterium that produces caproic acid, increased during the restoration process. Furthermore, a total of 18 metabolic pathways were enriched ( P  < 0.05) from DPM before and after restoration. This includes butanoate metabolism and pyruvate metabolism, which are related to the synthesis of key flavor esters in SFB. Graphical abstract: Image 1 Highlights: Bioremediation was employed to restore degraded pit mud used for Baijiu production. The microbial structure and function of degraded pit mud changed following restoration. The quality of Baijiu after restoration significantly improved.